2003
DOI: 10.1128/jcm.41.1.254-260.2003
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Methicillin-Resistant Staphylococcus aureus Directly from Sterile or Nonsterile Clinical Samples by a New Molecular Assay

Abstract: A rapid procedure was developed for detection and identification of methicillin-resistant Staphylococcus aureus (MRSA) directly from sterile sites or mixed flora samples (e.g., nose or inguinal swabs). After a rapid conditioning of samples, the method consists of two main steps: (i) immunomagnetic enrichment in S. aureus and (ii) amplification-detection profile on DNA extracts using multiplex quantitative PCR (5-exonuclease qPCR, TaqMan). The triplex qPCR assay measures simultaneously the following targets: (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
184
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 263 publications
(191 citation statements)
references
References 52 publications
3
184
0
4
Order By: Relevance
“…One of these barriers could be the presence of a capsule that reduces transformation efficiency. Indeed, agglutination assays have shown that the UAMS-1 strain is heavily capsulated (36). Moreover, preparation of competent cells requires the use of B2 medium supplemented with histidine, indicating that the growth conditions affect the constitution of the bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…One of these barriers could be the presence of a capsule that reduces transformation efficiency. Indeed, agglutination assays have shown that the UAMS-1 strain is heavily capsulated (36). Moreover, preparation of competent cells requires the use of B2 medium supplemented with histidine, indicating that the growth conditions affect the constitution of the bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of MSSA and MRSA from colonies suggestive of staphylococci were performed using standard methods 4 according to Clinical and Laboratory Standards Institute recommendations and confirmed with multiplex quantitative polymerase chain reaction (PCR) for the genes femA and mecA. 22 …”
Section: Microbiologic Methodsmentioning
confidence: 99%
“…The use of polymerase chain reaction (PCR) for screening can shorten this latency period considerably, more so than the use of culture on chromogenic agar. In our study, we quantified the impact on logistics and costs of replacing the use of culture on chromogenic agar with the use of rapid multiplex quantitative PCR (qPCR) 6,7 for the screening of previous MRSA carriers at hospital admission. Previous MRSA carriers are flagged by a computerized rapid alert system.…”
Section: Infect Control Hosp Epidemiol 2008; 29:1077-1079mentioning
confidence: 99%
“…During the intervention period, use of culture on chromogenic agar (MRSA ID; bioMerieux), which was the microbiological method normally used for MRSA screening, was replaced by the use of qPCR. 6 During both periods, samples were obtained on 2 consecutive days from the anterior nares and the groin using a cotton swab moistened with sterile saline solution.…”
Section: Infect Control Hosp Epidemiol 2008; 29:1077-1079mentioning
confidence: 99%